A single center retrospective study of paraneoplastic neurological syndromes with positive onconeural antibodies. (July 2021) - Fu, Peicai; He, Lilin; Tang, Na; Nie, Qing; Li, Zhijun
Graphical abstract: Highlights: Twenty-eight (51.8%) patients met the criteria for a definite PNS diagnosis. Associated cancer was confirmed in 13 (46.4%) definite PNS patients. Anti-CV2/CRMP5-Ab was the most frequently detectable onconeural antibodies. Peripheral neuropathy was the most common clinical symptom. Immunotherapy can be effective in treating specific PNS syndromes. Abstract: Paraneoplastic neurological syndromes (PNS) are rare immune-mediated disorders, and the detection of onconeural antibodies is helpful for PNS diagnosis. The aim of this study was to investigate the clinical characteristics of patients with PNS with positive onconeural antibodies in a single center in Hubei, China. We retrospectively analyzed the clinical characteristics of 54 patients with positive onconeural antibodies from January 2016 to September 2020. Among 780 patients with suspected PNS, 54 (6.9%) had positive onconeural antibodies. Of those 54 patients, 28 (51.8%) were diagnosed with definite PNS and 13 (24.1%) with possible PNS. Eighteen (33.3%) patients were confirmed with cancer. Ten PNS syndromes were detected among the 28 patients with definite PNS, and they had either classical (12/28, 42.8%) or non-classical syndromes (17/28, 60.7%). Peripheral neuropathy (9/28, 32.1%), subacute cerebellar degeneration (4/28, 14.3%), and limbic encephalitis (4/28, 14.3%) were the most common PNS syndromes. The anti-CV2/CRMP5-antibody was observed most frequently. Lung cancer was the most common tumor type. For patients with possible PNS, peripheral neuropathy was the most common PNS syndrome, and the anti-Tr-antibody was the most frequent onconeural antibody. Immunotherapy was effective in treating PNS. The anti-CV2/CRMP5-antibody was the most subsequently observed antibody. The manifestations of PNS are diverse and include peripheral neuropathy, subacute cerebellar degeneration, and limbic encephalitis. In patients with PNS, lung cancer was the most common tumor.